Sylloge tacticorum.
1 online resource
Keywords: "The Sylloge Tacticorum is a mid-Byzantine example of the literary genre of military manuals or Taktika which stretches back to antiquity. Compiled to record and preserve military strategies and tactics the manual discusses a wide variety of matters: battle formations, raids, sieges, ambushes and the distribution of booty. The Sylloge both reproduces material found in earlier texts and preserves a great deal of information about the military tactics being developed by the Byzantine army during the tenth century. This is the first complete translation of the Sylloge into English and it is accompanied by a glossary of the specialised Greek military vocabulary used in the work."--Provided by publisher.